1995
DOI: 10.1021/bi00048a004
|View full text |Cite
|
Sign up to set email alerts
|

HO.bul. and DNase I Probing of E.sigma.70 RNA Polymerase-.lambda.PR Promoter Open Complexes: Mg2+ Binding and Its Structural Consequences at the Transcription Start Site

Abstract: Chemical and enzymatic probing (footprinting) of the reactivity of the promoter DNA backbone is applied to characterize two binary open complexes RPo1 (-Mg2+) and RPo2 (+Mg2+), formed by Escherichia coli RNA polymerase (E sigma 70) at the lambda PR promoter. We report that HO. detects major differences in backbone reactivity between RPo1 and RPo2 in the open region from -4 to +1 relative to the transcription start site. Deoxyribose sugars at positions -4 to +1 of the t (template) strand react with HO. in RPo2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
126
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(141 citation statements)
references
References 51 publications
15
126
0
Order By: Relevance
“…We suggest this is in part due to the location of Ler binding, between positions 2221 and 260, and thus it is probable that this regulatory protein interacts with RNA polymerase, which binds to s 70 -dependent promoter regions extending from positions~255 to +20 in relation to the start of transcription (Craig et al, 1995). Perhaps consistent with this prediction, we have been unable to identify an additional negative-acting factor for LEE5 by using genetic approaches (data not shown).…”
Section: Discussionmentioning
confidence: 67%
“…We suggest this is in part due to the location of Ler binding, between positions 2221 and 260, and thus it is probable that this regulatory protein interacts with RNA polymerase, which binds to s 70 -dependent promoter regions extending from positions~255 to +20 in relation to the start of transcription (Craig et al, 1995). Perhaps consistent with this prediction, we have been unable to identify an additional negative-acting factor for LEE5 by using genetic approaches (data not shown).…”
Section: Discussionmentioning
confidence: 67%
“…Surprisingly, protection of DNA in I 1 from DNase I cleavage extends upstream only to Ϫ52 (template) on ''full-length'' P R , similar to what is observed in RP o (6). Because DNase I might displace weak upstream interactions in I 1 (8,9), other techniques are required to probe RNAP-DNA contacts in this transient intermediate. Sclavi et al (10) recently reported an elegant ''real-time'' footprinting study of RP o formation at the T7A1 promoter using x-ray-generated ⅐OH and rapid quench mixing.…”
mentioning
confidence: 70%
“…Additionally, the rapid rate of ⅐OH reaction with the DNA backbone means that fractional protection is approximately proportional to fractional occupancy for a short-lived, rapidly equilibrating intermediate like I 1 (10). By following the appearance of protection of the DNA backbone as a function of time (milliseconds to seconds) after mixing at 37°C, this study (10) circumvented potential issues raised by trapping promoter complexes at low temperature (11) and possible displacement of weak upstream interactions by DNase I (8,9).…”
mentioning
confidence: 99%
“…Studies in the E. coli enzyme suggest that this simple question can be complicated by the existence of multiple forms of open and closed complexes (31,41). It is tempting to use the fluorescence changes associated with DNA binding in a quantitative sense to determine the thermodynamic distribution between open and closed states.…”
Section: Estimation Of Fractional Meltingmentioning
confidence: 99%